Liraglutide attenuates cardiac remodeling and improves heart function after abdominal aortic constriction through blocking angiotensin II type 1 receptor in rats - Zheng RH; Bai XJ; Zhang WW; Wang J; Bai F; Yan CP; James EA; Bose HS; Wang NP; Zhao Z (Dove Medical Press, 2019)
Rong-Hua Zheng,1,2 Xiao-Jie Bai,1 Wei-Wei Zhang,1 Jing Wang,1 Feng Bai,1 Cai-Ping Yan,1 Erskine A James,3 Himangshu S Bose,4 Ning-Ping Wang,1,4 Zhi-Qing Zhao1,41Department of Physiology, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 2Department of Medicine, Linfen Vocational and Technical College, Linfen, Shanxi, People’s Republic of China; 3Department of Internal Medicine, Navicent Health, Macon, GA, USA; 4Basic Biomedical Sciences, Mercer University School of Medicine, Savannah, GA, USAObjective: Angiotensin II (Ang II) is known to contribute to the pathogenesis of heart failure by eliciting cardiac remodeling and dysfunction. The glucagon-like peptide-1 (GLP-1) has been shown to exert cardioprotective effects in animals and patients. This study investigates whether GLP-1 receptor agonist liraglutide inhibits abdominal aortic constriction (AAC)-induced cardiac fibrosis and dysfunction through blocking Ang II type 1 receptor (AT1R) signaling.Methods: Sprague-Dawley rats were subjected to sham operation and abdominal aortic banding procedure for 16 weeks. In treated rats, liraglutide (0.3 mg/kg) was subcutaneously injected twice daily or telmisartan (10 mg/kg/day), the AT1R blocker, was administered by gastric gavage.Results: Relative to the animals with AAC, liraglutide reduced protein level of the AT1R and upregulated the AT2R, as evidenced by reduced ratio of AT1R/AT2R (0.59±0.04 vs. 0.91±0.06, p<0.05). Furthermore, the expression of angiotensin converting enzyme 2 was upregulated, tissue levels of malondialdehyde and B-type natriuretic peptide were reduced, and superoxide dismutase activity was increased. Along with a reduction in HW/BW ratio, cardiomyocyte hypertrophy was inhibited. In coincidence with these changes, liraglutide significantly decreased the populations of macrophages and myofibroblasts in the myocardium, which were accompanied by reduced protein levels of transforming growth factor beta1, Smad2/3/4, and upregulated smad7. The synthesis of collagen I and III was inhibited and collagen-rich fibrosis was attenuated. Consistent with these findings, cardiac systolic function was preserved, as shown by increased left ventricular systolic pressure (110±5 vs. 99±2 mmHg, p<0.05), ejection fraction (83%±2% vs. 69%±4%, p<0.05) and fraction shortening (49%±2% vs. 35%±3%, p<0.05). Treatment with telmisartan provided a comparable level of protection as compared with liraglutide in all the parameters measured.Conclusion: Taken together, liraglutide ameliorates cardiac fibrosis and dysfunction, potentially via suppressing the AT1R-mediated events. These data indicate that liraglutide might be selected as an add-on drug to prevent the progression of heart failure.Keywords: angiotensin II AT1 receptor, cardiac fibrosis, cardiac function, liraglutide, telmisartan